1974
DOI: 10.1073/pnas.71.9.3522
|View full text |Cite
|
Sign up to set email alerts
|

A Ca ++ -Dependent and -Selective Ionophore as Part of the Ca ++ + Mg ++ -Dependent Adenosinetriphosphatase of Sarcoplasmic Reticulum

Abstract: Solubilized Ca++ + Mg++-dependent adenosinetriphosphatase (EC 3.6.1.3; ATP diphosphohydrolase) from sarcoplasmic reticulum increased bimolecular lipid membrane (oxidized cholesterol) conductance several hundred-fold. The relative conductance change and the relative permeability elicited by this material has the followingsequence:Ba++> Ca++ > Sr++ > Mg++> Mn++> Zn + +, Na +, K +, Cs +, Li +, and Rb +. Zn + + and Na + strongly inhibit the increase in Ca++ conductance obtained with solubilized Ca++ + Mg++-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 16 publications
3
41
0
Order By: Relevance
“…The purified ATPase is enzymatically inactivated by 50 /.~M Cd (MacLennan, 1970). Furthermore, when the purified solubilized ATPase functions as an ionophore in lipid membranes, Cd transport is negligible (A. E. Shamoo, personal communication), similar to published data for Zn (Shamoo and MacLennan, 1974).…”
Section: Mg Dependence Of Ca Uptake In Skinned Fiberssupporting
confidence: 66%
“…The purified ATPase is enzymatically inactivated by 50 /.~M Cd (MacLennan, 1970). Furthermore, when the purified solubilized ATPase functions as an ionophore in lipid membranes, Cd transport is negligible (A. E. Shamoo, personal communication), similar to published data for Zn (Shamoo and MacLennan, 1974).…”
Section: Mg Dependence Of Ca Uptake In Skinned Fiberssupporting
confidence: 66%
“…As shown in Fig. 2, the maximum effect is achieved with a final concentration of less than 10 ,g of subunit 9 added per ml. It may be assumed that only added protein taken up by the planar membrane was effective, because rinsing the compartment after the effect is complete does not modify the results.…”
Section: Resultsmentioning
confidence: 89%
“…Workers in several laboratories in recent years have attempted to identify protein fractions in mitochondria that exhibit proton ionophore activity (3)(4)(5)(6)(7)(8)(9)(10). Racker has shown that mitochondrial and chloroplast proteolipids may act as ionophores in collapsing proton gradients generated by bacteriorhodopsin (4), but it was not shown that these proteolipids were in fact associated with ATPase nor was any specific relation between ionophoric activity and biological function of this protein demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these studies deal with the effect of anionic detergents in the presence of monovalent cations. The effects of detergents on the conductivity and selectivity of membranes to divalent cations have not previously been dealt with, Our laboratory has a special interest in the effect of detergents on divalent cation conductance in black lipid membranes, since these detergents were used in the purification of proteins that possess ionophoric activity (Shamoo & MacLennan, 1974;Shamoo et al, 1976;Stewart et al, 1976 ;Abramson & Shamoo, 1978 ;Jeng, Ryan & Shamoo, 1978;Shamoo, 1978).…”
mentioning
confidence: 98%